The Clinical Characteristics and Surgical Outcomes of Epiblepharon in Korean Children: A 9-Year Experience - Jong Soo Kim; Sang Wook Jin; Mun Chong Hur; Yoon Hyung Kwon; Won Yeol Ryu; Woo Jin Jeong; Hee Bae Ahn (Journal of Ophthalmology)
Purpose. To examine the demographic characteristics, clinical features, surgical outcomes, and long-term prognoses of epiblepharon in Korean children. Methods. Epiblepharon patients who were followed for ≥ 6 month following surgical correction between January 2005 and December 2013. The patient demographics, clinical features, concomitant disorders, surgical outcomes, and complications were retrospectively reviewed. Results. A total of 768 epiblepharon records were included in the analysis. The mean patient age was 6.55±2.37 years. At presentation, 712 patients (92.8%) complained of typical epiblepharon symptoms. The mean patient age at surgery was 6.95±2.52 years, with 629 patients (81.9%) on the lower lid and 72 patients (9.4%) on the upper lid and 82 patients (10.7%) undergoing surgery on both lids. The eyelid was well everted with no recurrence in 740 patients (96.4%). Conclusion. Epiblepharon frequently occurs in Korean children and is correctable with a simple surgery. Recurrence and serious complications do not occur often, and any suspicions of epiblepharon should be investigated. A thorough ocular examination can lead to a correct diagnosis and timely corrective surgery. Most procedures are successful and prevent secondary complications that often occur with uncorrected epiblepharon.